Eravacycline, a novel tetracycline derivative, does not induce Clostridioides difficile infection in an in vitro human gut model. (15th September 2020) - Buckley, Anthony M; Altringham, James; Clark, Emma; Bently, Karen; Spittal, William; Ewin, Duncan; Wilkinson, Vikki; Davis, Georgina; Moura, Ines B; Wilcox, Mark H
Abstract: Objectives: The approval of new antibiotics is essential to combat infections caused by antimicrobial-resistant pathogens; however, such agents should be tested to determine their effect on the resident microbiota and propensity to select for opportunistic pathogens, such as Clostridioides difficile . Eravacycline is a new antibiotic for the treatment of complicated intra-abdominal infections. Here, we determined the effects of eravacycline compared with moxifloxacin on the microbiota and if these were conducive to induction of C. difficile infection (CDI). Methods: We seeded in vitro chemostat models, which simulate the physiological conditions of the human colon, with a human faecal slurry and instilled gut-reflective concentrations of either eravacycline or moxifloxacin. Results: Eravacycline instillation was associated with decreased Bifidobacterium, Lactobacillus and Clostridium species, which recovered 1 week after exposure. However, Bacteroides spp. levels decreased to below the limit of detection and did not recover prior to the end of the experiment. Post-eravacycline, a bloom of aerobic bacterial species occurred, including Enterobacteriaceae, compared with pre-antibiotic, which remained high for the duration of the experiment. These changes in microbiota were not associated with induction of CDI, as we observed a lack of C. difficile spore germination and thus no toxin was detected. Moxifloxacin exposure sufficiently disrupted the microbiota to induce simulated CDI, where C. difficile spore germination, outgrowth and toxin production were seen. Conclusions: These model data suggest that, despite the initial impact of eravacycline on the intestinal microbiota, similar to clinical trial data, this novel tetracycline has a low propensity to induce CDI.